Analisa Pengendalian Persediaan Suku Cadang Pada PT. XYZ Dengan Metode Analisis ABC - Eka Sofia. A; Darno Darno; Mitha Otik Wiraswati; Dewi Agustya Ningrum (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2020)
Inventory can be interpreted as a stock of goods to be sold or used at a certain time,without the inventory the company will run the risk and can not meet costomer demand. This research was conducted to analyze spare part inventory using ABC analysis method and EOQ method at PT. Adiprima Suraprinta, Gresik.The results of this study are there there are 4 spare parts inventory items in group A with a cumulative percentage of 8,59% by absorbing a budget of 56,78%, there are 5 spare parts inventory items in group B with a cumulative percentage of 18,47% by absorbing a budget of 24,15%, there are 17 spare parts inventory items in group C with a cumulative percentage of 72,92% by absorbing a budget of 10%.